ASSOCIATION OF FORWARD HEAD POSTURE WITH NECK PAIN AMONG BANKERS OF HAYATABAD PESHAWAR: A CROSS SECTIONAL SURVEY (The Research of Medical Science Review, 2024)
Background: Different factors such as prolong sitting at work or abnormal posture of head during work may have great role in occurrence of neck pain among those who use computer. In literature forward head posture has not always been associated with neck pain. Objective: To determine the association between forward head posture with neck pain among bankers of Hayatabad Peshawar, Pakistan. Methods: It was cross sectional study to explore association between forward head posture and neck pain.86 bankers were examine using photogrammetry method and web plot digitizer software for plotting angle on digital image. Numeric pain rating scale and neck disability index questionnaire was use to measure neck pain and intensity. Results: Most of the participants 80.2% had forward head posture. Majority 47.7% were in age between 20-30 and having mean age 33.8±8.8. The mean score of neck disability index was 5.88±4.9. The chi square test showed no significant association (P>0.05) between forward head posture and neck pain. Conclusion: This study concluded that forward head posture is quite common in bankers but there is no association between forward head posture and neck pain.